Disruption of PHO13 improves ethanol production via the xylose isomerase pathway - Bamba, Takahiro; Hasunuma, Tomohisa; Kondo, Akihiko (AMB Express, 2016)
Xylose is the second most abundant sugar in lignocellulosic materials and can be converted to ethanol by recombinant Saccharomyces cerevisiae yeast strains expressing heterologous genes involved in xylose assimilation pathways. Recent research demonstrated that disruption of the alkaline phosphatase gene, PHO13 , enhances ethanol production from xylose by a strain expressing the xylose reductase (XR) and xylitol dehydrogenase (XDH) genes; however, the yield of ethanol is poor. In this study, PHO13 was disrupted in a recombinant strain harboring multiple copies of the xylose isomerase (XI) gene derived from Orpinomyces sp., coupled with overexpression of the endogenous xylulokinase (XK) gene and disruption of GRE3 , which encodes aldose reductase. The resulting YΔGP/XK/XI strain consumed 2.08 g/L/h of xylose and produced 0.88 g/L/h of volumetric ethanol, for an 86.8 % theoretical ethanol yield, and only YΔGP/XK/XI demonstrated increase in cell concentration. Transcriptome analysis indicated that expression of genes involved in the pentose phosphate pathway ( GND1 , SOL3 , TAL1 , RKI1 , and TKL1 ) and TCA cycle and respiratory chain ( NDE1 , ACO1 , ACO2 , SDH2 , IDH1 , IDH2 , ATP7 , ATP19 , SDH4 , SDH3 , CMC2 , and ATP15 ) was upregulated in the YΔGP/XK/XI strain. And the expression levels of 125 cell cycle genes were changed by deletion of PHO13 .